Morphological and phenological strategies for flooding tolerance in Cerrado and Pantanal trees: implications for restoration under new legislation. Issue 1 (1st April 2022) - Bogarín, Marcia R. A.; Reis, Letícia K.; Laura, Valdemir A.; Pott, Arnildo; Szabo, Judit K.; Garcia, Letícia C.
Abstract : In 2012, the Native Vegetation Protection Law 12, 651 decreased the extent of Areas of Permanent Preservation in Brazil. While previously the distance from water was measured during the rainy season, the new version only considered the extent of the regular watercourse. This change affects conservation and restoration sites, and restoration programs need to be modified based on the new legislation. For instance, more flood‐tolerant species need to be planted, given the higher probability that restoration efforts will be lost during flooding. To identify species suitable for the restoration of such areas, we tested if plants that develop morphological structures to tolerate waterlogging stress are more resistant to hypoxia caused by flooding and can recover better afterwards. We experimentally evaluated survival and morphological or phenological strategies (root dry mass, height, basal diameter, adventitious roots, lenticels, and leaf renewal) of 13 tree species from the Cerrado and Pantanal biomes of Brazil. After 56 days of simulated inundation and 56 days of post‐inundation recovery, we found that all study species were able to survive on waterlogged soil and to recover after the flood, and they can be used to restore periodically flooded riparian forests within the new legal zone. Our study is particularly relevant, as climate change is expected to increase flooding. As environmental laws change and new areas get restored including those in artificially flooded areas, such as on banks of hydroelectric dams, the experimental approach introduced in this study should be replicated with other species from various phytogeographic domains worldwide.